TRANSFORMASI PROSES BISNIS INTERNAL INSTANSI PENDIDIKAN/RELAWAN MELALUI ERP SEDERHANA UNTUK EFISIENSI OPERASIONAL - Yohan Purnawan; Melisa Nur Asima Sidabutar; William Gerry Sidabutar (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service Program (PKM) activity aims to improve the operational efficiency of educational institutions/volunteers through the transformation of internal business processes with the implementation of a simple ERP based on easy-to-adopt tools (e.g., Google Workspace/Microsoft 365, open-source applications, or standardized sheets). Common problems that arise include duplicate records, scattered data, manual approval processes, difficult document tracking, late reporting, and low cost and inventory visibility. Interventions are carried out through as-is process mapping, to-be process design, preparation of data standards (master data), development of simple ERP modules (finance, correspondence, assets & inventory, procurement/logistics, programs/activities), user training, and go-live and improvement assistance. The outputs are a simple ERP blueprint, SOPs, form and dashboard templates, and impact reports (processing time, report accuracy, reduced errors).